Evaluation of Bio M pylori serologic test and C-13 urea breath test for H. pylori infection in children with recurrent abdominal pain: a pilot study - Mira Dewita; Badriul Hegar Syarif; Sudigdo Sastroasmoro (Indonesian Pediatric Society Publishing House, 2010)
Background Diagnosing Helicobacter pylori infection in children is still a problem. Urea breath test is the gold standard for noninvasive diagnostic test, but it is expensive and not available in most hospitals. The Bio M Pylori serologic test has good diagnostic value in adults, less expensive and more practical, but had never been evaluated in children. Objective To determine the prevalence of H. pylori infection and the diagnostic accuracy of Bio M Pylori serologic test in children with recurrent abdominal pain. Methods This study was conducted in May - June 2009. Children aged 12-15 years with recurrent abdominal pain were examined with urea breath test and the Bio M Pylori serologic test. Sensitivity, specificity, area under the curve (AUC), predictive values, and likelihood ratios were calculated for the Bio M Pylori serologic test. Results Most subjects aged 13 years (83%). Girls outnumbered boys, and most were undernourished. The prevalence ofH. pylori infection detected by urea breath test and Bio M Pylori serologic test was 8% and 52%, respectively. The Bio M Pylori serologic test had sensitivity and specificity of 100% and 53%, respectively. Area under the curve (AUC) was 0.764. Positive and negative predictive values were 16 and 100%, whereas positive and negative likelihood ratios are 2.12 and 0. The overall accuracy of this test is 5 7% Conclusions The Bio M Pylori serologic test has high sensitivity value (100%). This diagnostic kit can be considered as a good pre-endoscopic screening tool in children with recurrent abdominal pain caused by H. pylori infection.